2000
DOI: 10.21273/hortsci.35.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Cracking of a Susceptible, an Intermediate, and a Resistant Sweet Cherry Cultivar

Abstract: Fruit were studied to determine if anatomical and physiological features explain the difference in susceptibility to rain-induced cracking of the sweet cherry (Prunus avium L.) cultivars Sue (resistant), Lapins (moderately resistant), and Van (susceptible). Water uptake as a percentage of fruit weight at cracking tended to be high in `Sue', medium in `Lapins', and low in `Van' and was related to the percentage of cherries remaining sound after 4 hours of immersion, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 15 publications
(13 reference statements)
2
21
0
2
Order By: Relevance
“…Lane et al (2000) reported that Ca content in the epidermis of 'Sue' (resistant) was lower than in 'Van' (susceptible), and there was no difference of Ca content in the hypodermal cells between the two cultivars. It is possible that other factors such as anatomical, physiological, and genetic characteristics have a greater influence than Ca in determining splitting resistance differences between these cultivars (Balbontín et al, 2013;Christensen, 1996).…”
Section: Tissue Ca Content Is Correlated To Fruit Pectin Release Ratementioning
confidence: 97%
See 1 more Smart Citation
“…Lane et al (2000) reported that Ca content in the epidermis of 'Sue' (resistant) was lower than in 'Van' (susceptible), and there was no difference of Ca content in the hypodermal cells between the two cultivars. It is possible that other factors such as anatomical, physiological, and genetic characteristics have a greater influence than Ca in determining splitting resistance differences between these cultivars (Balbontín et al, 2013;Christensen, 1996).…”
Section: Tissue Ca Content Is Correlated To Fruit Pectin Release Ratementioning
confidence: 97%
“…However, Glenn and Poovaiah (1989) revealed that a reduction in splitting potential of 'Bing' cherries by CaCl 2 at 2.5 mM (0.028%) was a result of increased splitting threshold and not a reduction in water absorption. Lane, Meheriuk, and Mckenzie (2000) reported that the water uptake threshold at which the fruit split (splitting threshold) is a major factor explaining the difference in splitting resistance of three cultivars ['Sue' (resistant), 'Lapins' (moderately resistant), and 'Van' (susceptible)]. This research indicated that the reduction in splitting potential by CaCl 2 at 0.2-2.0% at 0°C appeared to be a result of both reduction in water absorption rate and an increase in splitting threshold for the cultivars of 'Skeena' and 'Bing'.…”
Section: Effect Of Cacl 2 In Cold Water On Fruit Splitting Potentialmentioning
confidence: 99%
“…In a study, Emmons and Scott (1998) and Matas et al (2004) found that the cracking-resistant genotype of tomato had a thicker epidermal and cuticle layer than the sensitive genotype. In contrast, Lane et al (2000) suggested the skin's role in cracked resistance is related to the calcium content of the epidermis cells which increase the cell's integrity. This difference in the results might be reasoned to different mechanisms in fruits cracking.…”
Section: Fruit Morphologymentioning
confidence: 98%
“…In previous researches, have been reported the effect of fruits' morphological properties on cracking rate and intensity in agricultural crops; such as greenhouse tomato (Hetzroni et al, 2011;Lichter et al, 2002;Matas et al, 2004), sweet cherry (Lane et al, 2000), apple (Kasai et al, 2008), nectarine (Gibert et al, 2007). However, there is not exact information on how these factors affect cracking because of the complexity of influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…Another very significant parameter is the resistance to cracking, which produces important economic losses. Cracking occurs during periods of high atmospheric humidity, when a large difference in water potential between tree and fruit can cause movement of water from the branches and leaves into the fruit . It can be caused by both external (environmental conditions) and internal (fruit characteristics) influences.…”
Section: Introductionmentioning
confidence: 99%